Analysis of the Effect of Female Genital Tuberculosis on Ovarian Reserve Parameters - Sharma Richa; Kanhere Anjali; Jain Sonal; Jain Akrati (Journal of Human Reproductive Sciences)
Background: Female genital tuberculosis (FGTB) is a known cause of female infertility. Worldwide incidence is 5%–10% and annual burden in India is around 4%–7%. It is known to cause tubal and endometrial damage. However, the effect on ovarian damage is poorly known. The availability of ovarian markers has contributed to an improved understanding of ovarian reserve in FGTB. Aims: The aim of this study was to assess ovarian reserve by measuring anti-Mullerian hormone (AMH) and antral follicle count (AFC) amongst infertile women and analyse the effect of GTB on ovarian reserve parameters. Settings and Design: This was a prospective study at a tertiary referral centre for infertility for 18 months. Materials and Methods: A total of 133 infertile women who underwent diagnostic hysterolaparoscopy and cartridge-based nucleic acid amplification test testing of an endometrial biopsy were included in the study. AMH and AFC of all the infertile women were assessed and compared between cases with and without FGTB. Statistical Analysis Used: Independent t-test was used to find the outcome differences in the distribution of values. P < 0.05 was considered statistically significant. Results: Fifty-eight (43.6%) cases were diagnosed with FGTB (Group I), and 75 (56.3%) cases were without FGTB (Group II). The mean AMH level 1.88 ng/ml (±1.52) and mean AFC 9.0 (±5.50) were significantly lower (P < 0.001) in Group I than in Group II with AMH 3.57 ng/ml (±2.93) and AFC 12.50 (±6.0). Conclusion: In women with prolonged infertility and low ovarian reserve, FGTB should be ruled out. Early diagnosis and treatment of GTB may prevent further decline of ovarian reserve and improve the reproductive outcome.